Analisis Komparasi Pendapatan Agroindustri Gula Aren dan Gula Semut (Studi Kasus Kelompok Tani Mutiara Di Kecamatan Lareh Sago Halaban Sumatera Barat) - Yelfiarita Yelfiarita; Wimby Filiani; Veronice Veronice (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2022)
Nira is the main derivative product of Aren palm. Making Aren palm to be palm sugar and granulated palm sugar will increase the benefit of Aren Palm and increase the farmer's income. It is needed towards perform comparison research for agroindustrial revenue of palm sugar and granulated palm sugar to make sure that it may be a referral for the farmer in picking an extra rewarding diversification of Aren palm. This research strives to review the incorporated revenue from palm sugar and granulated palm sugar services and examine the evaluation of the usefulness amount of palm sugar and granulated palm sugar services. The study was performed in January - April 2021 for all participants of the